A taste of youth: Seasonal changes in the diet of immature white sharks in eastern Australia - Lipscombe, Rebecca S.; Meyer, Lauren; Butcherine, Peter; Morris, Stephen; Huveneers, Charlie; Scott, Anna; Butcher, Paul A. (Frontiers in Marine Science, 2024)
White sharks (Carcharodon carcharias) play a crucial ecological role, shaping ecosystems through direct predation and risk effects. On the east coast of Australia, immature white sharks are broadly distributed, inhabiting a wide range of habitats and ecosystems from temperate Tasmania to tropical North Queensland. Using stable isotopes and fatty acids of muscle and plasma, we examined the diet and habitat use of 136 immature white sharks (152–388 cm total length) captured on SMART drumlines on the East Australian coast. This facilitated the temporal assessment of white shark trophic ecology from a few weeks to approximately a year. Biochemistry of muscle samples showed that white sharks predominantly feed on low trophic level prey from coastal environments. A seasonal shift in diet was evident, with the increasing proportions of essential fatty acids in muscle tissues during spring and summer suggesting a greater consumption of high-nutrition preys during those months compared to autumn and winter. By combining stable isotope and fatty acid analysis, we gain a comprehensive understanding of immature white shark diet in eastern Australia. Our results confirm that white sharks are generalist predators that exhibit seasonal shifts in their diet. Their high use of coastal habitats reinforces the importance of these areas for foraging, which is crucial for growth and development during this critical life stage.